2016
DOI: 10.1002/2015gb005214
|View full text |Cite
|
Sign up to set email alerts
|

Global impact of tropical cyclones on primary production

Abstract: International audienceIn this paper, we explore the global responses of surface temperature, chlorophyll, and primary production to tropical cyclones (TCs). Those ocean responses are first characterized from the statistical analysis of satellite data under ~1000 TCs over the 1998–2007 period. Besides the cold wake, the vast majority of TCs induce a weak chlorophyll response, with only ~10% of induced blooms exceeding 0.1 mg m. The largest chlorophyll responses mostly occur within coastal regions, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 29 publications
7
58
2
Order By: Relevance
“…The SST cooling induced by rains might have been observed during the days before the hurricane passage given the high DAP anomalies at this time ( Figure 3B). Yet, though it has been reported that SST starts to decrease at day -3 (Vincent et al, 2012b;Menkes et al, 2016), we found that this occurred only from the day 0 on ( Figure 3C). Thus, the DAP effects did not seem to have been sufficient to cool the waters of the EEZ.…”
Section: Regression Analysescontrasting
confidence: 73%
See 2 more Smart Citations
“…The SST cooling induced by rains might have been observed during the days before the hurricane passage given the high DAP anomalies at this time ( Figure 3B). Yet, though it has been reported that SST starts to decrease at day -3 (Vincent et al, 2012b;Menkes et al, 2016), we found that this occurred only from the day 0 on ( Figure 3C). Thus, the DAP effects did not seem to have been sufficient to cool the waters of the EEZ.…”
Section: Regression Analysescontrasting
confidence: 73%
“…In previous studies of other regions, researchers considered different spatial scales to assess the TCinduced oceanographic variability. For example, Babin et al (2004) constructed cells of 0.5 • latitude north and south and 1 • longitude west and 2 • longitude east for each hurricane track point analysed, while other authors have used 200 km radius disks centered at the consecutive TC positions (Menkes et al, 2016;Shropshire et al, 2016) and square areas of different sizes located at variable distances from the TC trajectory (Wang and Zhao, 2008;Merritt-Takeuchi and Chiao, 2013). On the other hand, Son et al (2007) and Farfán et al (2014) analysed a band of 700 km and 15 km wide, respectively, centered on storm tracks, while Foltz et al (2015) and Parker et al (2017) assessed TC activity across a large region of the Western Subtropical North Atlantic and the Great Barrier Reef of Australia, respectively.…”
Section: Spatial and Temporal Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytoplankton living in tropical oligotrophic water is sensitive to nutrient enhancement (Cloern & Jassby, ). Modeling results suggested that the tropical cyclone‐induced phytoplankton blooms in north‐western Australia could contribute to 20% of annual primary production (Menkes et al, ). The shift changes of diatoms and dinoflagellates in the three locations were asynchronous after the 1970s, which might be related to their different geographic and hydrologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For each grid cell with a spatial resolution of 1° latitude × 1° longitude (≈12,345 km 2 at the equator, Figure 1), the energy released by TCs was computed as the power dissipated by friction in the surface layer (Emanuel, 2005) following Menkes et al (2016) and . At each point, the maximum 10-min sustained wind speeds at 10 m above the ground (V) was extracted from the database.…”
Section: Cyclonesmentioning
confidence: 99%